Evaluation of body composition, muscle strength and balance in adolescent soccer players - Erkut Atilgan, O.; Sirmen, B.; Uzun, S.; Ramazanoglu, N.; Akan, I.; Atil, Z. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Soccer requires high leg strength, fit body composition and good postural control especially unipedal posture. In this research, we aim to investigate whether there are relationship between strength (muscle strength and muscle lean mass) and balance (static and dynamic) in soccer players. Materials and Methods: 17 soccer players (mean: age=15 height=168,5 weight=65,5 BMI=20,8 training years=4,6) were participated in the study. Legs strength was measured with leg dynamometer; body composition was measured x-scan body composition analyzer. Balance (static and dynamic) was measured Prokin 5.0 Technobody. Static stabilometery tests were done as Opened Eyes (EO) and Closed Eyes (EC) with 30 second duration. Dynamic Stabilometery Tests: a) Slalom test (forward-backward) to one axis a time. The subject`s scope is to hit objectives and follow the blue ideal line within 60 sn duration (a-hold with two hand and b-without hold) with 5 hard degree. b) Unilateral dynamic-stance tests (left and right leg) was done with the controlled load monoaxial test (antero-posterior) for right and left foot with 10 repetitions on an axis controlling player`s load (5 hard). Results: Correlation was done between strength (muscle strength and muscle lean mass) and balance (static and dynamic) in soccer players. There were significant relationship Static Romberg Test EC/EO Perimeter Ratio and Left leg, right leg, trunk lean mass. No significant correlations were found between dynamic tests and body composition. There are high negative correlation between lean mass percent and fat percent of soccer players. Thus; this players have enough fit condition for their branches. Besides, there are high correlations among leg strength and legs (left and right), trunk lean mass. Left and right leg lean mass, left and right leg perimeter error scores for anterior-posterior dynamic balance were compared with paired samples T-test. Left lean mass is better than right lean mass (p<0.05), similarly, left leg dynamic balance was greater than right leg dynamic balance (p<0.01). Conclisions: As a result, increases back and leg muscle lean mass and strength is associated with better postural stability, there should be further research for the balance evaluations after the strength training program for different sports.